2004
DOI: 10.1103/physrevlett.92.133901
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Two-Dimensional Vector Solitons

Abstract: In this Letter, we introduce the concept of stabilized vector solitons as nonlinear waves constructed by the addition of mutually incoherent fractions of Townes solitons that are stabilized under the effect of a periodic modulation of the nonlinearity. We analyze the stability of these new kinds of structures and describe their behavior and formation in Manakov-like interactions. Potential applications of our results in Bose-Einstein condensation and nonlinear optics are also discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
48
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…It has been recently shown that a modulation of the nonlinearity along the propagation direction in the optical material can be used to prevent the collapse of two-dimensional laser beams [4]. The concept has been extended to the case of several incoherent optical beams [5] and to the case of matter waves [6].In this paper we use a similar idea to stabilize against collapse pulsed laser beams propagating in planar waveguides. This configuration is of great importance, as it is the common experimental procedure used for exciting spatial optical solitons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that a modulation of the nonlinearity along the propagation direction in the optical material can be used to prevent the collapse of two-dimensional laser beams [4]. The concept has been extended to the case of several incoherent optical beams [5] and to the case of matter waves [6].In this paper we use a similar idea to stabilize against collapse pulsed laser beams propagating in planar waveguides. This configuration is of great importance, as it is the common experimental procedure used for exciting spatial optical solitons.…”
mentioning
confidence: 99%
“…It has been recently shown that a modulation of the nonlinearity along the propagation direction in the optical material can be used to prevent the collapse of two-dimensional laser beams [4]. The concept has been extended to the case of several incoherent optical beams [5] and to the case of matter waves [6].…”
mentioning
confidence: 99%
“…In that way, a propagating beam focuses and expands in alternating regions and becomes stabilized in average. This idea has been further explored in [10,11,12,13,14,15].…”
mentioning
confidence: 99%
“…In the region of stable propagation the vortex amplitude slowly decays due to the emission of radiation until a stabilized vector soliton is formed. In this process, both components emit radiation to readjust their norms to satisfy the relation I 1 + I 2 = I T ownes [15]. From Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation